4,4′-(Cyclohexane-1,1-diyl)diphenol methanol solvate - Shuai, Jun (International Union of Crystallography, 2009)
The title compound, crystallized as a methanol solvate, C(18)H(20)O(2)·CH(3)OH, is an intermediate in the synthesis of the antilipidemic agent clinofibrate. Molecules are packed together with the methanol solvent molecule via two O—H⋯O hydrogen bonds. The third O—H⋯O hydrogen bond is between neighboring 4,4′-(cyclohexane-1,1-diyl)diphenol molecules. The dihedral angle between two benzene rings planes is 81.69 (6).